2020
DOI: 10.4102/ojvr.v87i1.1837
|View full text |Cite
|
Sign up to set email alerts
|

Study on the prevalence and genetic diversity of Eimeria species from broilers and free-range chickens in KwaZulu-Natal province, South Africa

Abstract: This study was conducted from January to October 2018 with the objective to determine the prevalence and genetic diversity of Eimeria species in broiler and free-range chickens in KwaZulu-Natal province, South Africa. A total of 342 faecal samples were collected from 12 randomly selected healthy broiler chicken farms and 40 free-range chickens from 10 different locations. Faecal samples were screened for the presence of Eimeria oocysts using a standard flotation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
5
0
2
Order By: Relevance
“…was observed, 59, together with a diversity of eight species of Eimeria . in South Africa, Fatoba et al ( 25 ) observed that 46.3% of the farms were positive for coccidian infections. In a similar study carried out in Tunisia by Kaboudi et al ( 6 ), a prevalence of 31.8% was observed for coccidia of the genus Eimeria spp., and the species E. maxima, E. tenella and E. acervulina were characterized through their morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was observed, 59, together with a diversity of eight species of Eimeria . in South Africa, Fatoba et al ( 25 ) observed that 46.3% of the farms were positive for coccidian infections. In a similar study carried out in Tunisia by Kaboudi et al ( 6 ), a prevalence of 31.8% was observed for coccidia of the genus Eimeria spp., and the species E. maxima, E. tenella and E. acervulina were characterized through their morphology.…”
Section: Discussionmentioning
confidence: 99%
“…According to Flores et al ( 31 ), the high prevalence and diversity, associated with indiscriminate use of anticoccidials are responsible for severe drug resistant Eimeria species in Korean chicken farms. Mixed infection, according to Fatoba et al ( 25 ), is very common: it causes increased pathogenicity and is a threat to vaccine control. This information also demonstrates the failure of zootechnical control and the low quality of animal management, in which the animals lost weight.…”
Section: Discussionmentioning
confidence: 99%
“…No que diz respeito a análise parasitológica para pesquisa de Eimeria spp., do total de 124 amostras de intestino de frangos caipiras, 92 (74,19%) tiveram a presença do agente (Tabela 1), com contagens que variaram de 100 a 18.800 oocistos por amostra. Os resultados indicam a alta ocorrência de aves infectadas por Eimeria spp., sendo considerados superiores aos estudos de ocorrência de oocistos do parasita em frangos caipiras nas cidades de Porto Alegre, RS, no Brasil (55,4%; Siqueira e Marques, 2016), Shidi Tab, na Tunísia (31,8%; Kaboudi et al, 2016) e província de KwaZulu-Natal, África do Sul (59,5%; Fatoba et al, 2020).…”
Section: Resultsunclassified
“…Apesar da alta ocorrência de oocistos de Eimeira spp. em amostras de intestinos de frangos caipiras, as manifestações clínicas foram ausentes (Gráfico 1), corroborando de que a coccidiose subclínica é predominante em aves de sistemas caipiras (Kaboudi et al, 2016;Fatoba et al, 2020). O grau de severidade da coccidiose depende da carga parasitária, da capacidade imunológica, idade do hospedeiro e patogenicidade do parasita, relacionado principalmente a espécie de Eimeira (Quiroz-Castañeda e Dantán-González, 2015).…”
Section: Resultsunclassified
“…Infections with several Eimeria species are very common on farms [42,43]. Gyorke et al (2013) describe that in our neighbouring country, Romania, there are mixed infections, usually with two, three or four different types of Eimeria [22].…”
Section: Discussionmentioning
confidence: 99%